Effect of postpartum clinical guideline on maternal outcomes in iranian women: a randomized controlled clinical trial - Leila Abdoli Najmi; Sakineh Mohammad-Alizadeh-Charandabi; Shayesteh Jahanfar; Fatemeh Abbasalizadeh; Haniyeh Salehi Poormehr; Mojgan Mirghafourvand (BMC Pregnancy and Childbirth)
Abstract Background The postpartum period is a vital time for women, infants, spouses, parents, caregivers and families. Considering the importance of postpartum care and the necessity of using comprehensive and up-to-date clinical guidelines in Iran, this study was designed to implement a indigenized clinical guideline in Iran on maternal outcomes, including maternal functioning, postpartum depression and postpartum specific anxiety (primary outcomes) as well as infant care, maternal health problems, experiencing violence, feeding method and contraception use (secondary outcomes). Methods This randomized controlled trial was conducted with 272 postpartum women in Taleghani and Alzahra hospitals in Tabriz in 2023. Participants were randomly allocated to intervention and control groups. The intervention group received care and training based on clinical guideline while the control group received routine care and training. Both groups were followed up by telephone at the second and sixth week after delivery. Questionnaires assessing maternal health problems and postpartum depression were completed in the second and sixth weeks and while assessments of maternal functioning, postpartum depression, postpartum specific anxiety, infant care behavior, and experiences of violence were conducted in the sixth week after delivery. ANCOVA, independent-t tests, and Mann-Whitney U tests were used for data analysis. Results There was no significant difference between the two groups regarding of socio-demographic characteristics (P < 0.05). Additionally, there were no significant differences in the mean score of maternal functioning, anxiety, depression, infant care behavior or experiences of violence after the intervention between the intervention and control groups based on ANCOVA or Mann-Whitney U tests (P < 0.05). However, the rate of infant formula use was significantly lower in the intervention group (12.9%) compared to the control group (23.4%) (P = 0.027). In terms of contraceptive methods used, 24.3% of the intervention group and 22.2% of the control group reported using reliable contraceptive methods )P = 0.035(. Furthermore, 98.5% of participants in the intervention group expressed satisfaction with the education and recommendations provided, compared to 88.2% in the control group (P = 0.002). Conclusion Providing clinical guideline-based care was associated with increased breastfeeding rates, greater use of reliable contraception methods, and higher levels of maternal satisfaction. However, it did not have a significant impact on other maternal outcomes. Trial registration Iranian Registry of Clinical Trials (IRCT) IRCT20120718010324N76 Date of registration 27/1/2023. URL https://trialsearch.who.int/Trial2.aspx? TrialID IRCT20120718010324N76 Date of first registration 27/3/2023.